The Relationship Between Fear Of Missing Out With Problematic Internet Use In K-Pop Fans - Ristia Ananda; Pundani Eki (Journal of Social and Industrial Psychology, 2024)
The emerging Korean Wave phenomenon is known to have affected all groups, both teenagers and adults and is supported by the rapid development of information technology. So the internet has an important role in connecting fans with K-Pop artists or celebrities. K-pop fans will check their social media accounts for hours to find the latest information about their idols, thus interfering with other activities. The impact of internet dependence and addiction affects physical and psychological conditions and other aspects of life so this behavior can be categorized as Problematic Internet Use (PIU) behavior. One of the factors that cause PIU is Fear of Missing Out (FoMO). This study aims to determine the relationship between K-pop fans' fear of missing out and problematic internet use. This study uses quantitative methods with quota sampling techniques. The number of samples in this study was 318 people. The analysis technique used is correlation using statistical software. The results of the analysis show that there is a relationship between fear of missing out and problematic internet use in K-pop fans. If the fear of missing out is high, problematic internet use is also high.